Impact of Nurse Residency Programs on Retention and Job Satisfaction: An Integrative Review - McGregor, Heather M.; Scott, Morgan; Gorham, Robyn; Hunt, Elena (European Scientific Journal, ESJ, 2024)
Objects: Retention of new nurses is vital within the context of the nursing shortage Canada is currently facing. Nurse residency programs (NRP) need to be explored to better understand their role in combating the nursing shortage. The aim of this study is to explore current nurse residency programs and their impacts on retention and job satisfaction with the aim to inform development of similar programs in Canada. Methods: The study utilized Whittemore and Knafl’s integrative review methodology to review current literature on nurse residency programs in The United States of America with focuses on retention rates, job satisfaction and intent to leave. Overall, this article drew on seven distinct research studies. Findings: The literature review found that Nurse Residency Programs (NRP) can improve retention rates however, this may be due to contracts signed upon beginning of NRP. Job satisfaction for newly licensed registered nurses (NLRNs) participating in NRP also showed improvements but their impact on reducing turnover intention is unclear and needs further study. Conclusion: The impact of nurse residency programs on retention and job satisfaction has some positive effects, but the strength of this relationship remains unclear and would benefit from further research.